Immune profiling of lupus miliaris disseminatus faciei and successful management with anti‐tumour necrosis factor therapy. (1st July 2021) - Alexanian, C.; Liakos, W.; Toussi, A.; Kao, J.; Cheng, M. Y.; Wang, E. A.; Nava, J.; Tran, M.; Marusina, A. I.; Merleev, A. A.; Leal, A. R.; Fung, M. A.; et al.
Summary: Lupus miliaris disseminatus faciei (LMDF) is a chronic inflammatory dermatosis of unknown aetiology, most often seen in young adults. Although many treatments for LMDF exist, treatment guidelines have not been developed, and response to therapy is generally unpredictable. We present the results of transcriptomic analysis of LMDF lesional skin, which revealed a variety of differentially expressed genes linking LMDF to alterations in innate and adaptive T helper 1 immunity. Immunohistochemical analysis was also performed, identifying similar changes in T‐cell immune responses. Given evidence for increased tumour necrosis factor (TNF) pathway activity, our patient, who had previously been refractory to multiple treatments, was initiated on TNF inhibitor therapy with excellent response. This characterization of the LMDF immune response may lead to improved treatment of this condition.